High‐performance natural rubber latex composites developed by a green approach using ionic liquid‐modified multiwalled carbon nanotubes. Issue 38 (22nd September 2018) - Ge, Yi; Zhang, Qianyun; Zhang, Yandan; Liu, Fusheng; Han, Jingjie; Wu, Chifei
ABSTRACT: The effect of multiwalled carbon nanotubes (MWCNTs) modified by a hydrophilic ionic liquids (ILs), including 1‐ethyl‐3‐methylimidazolium bromide and 1‐hexyl‐3‐methylimidazolium bromide, was studied. The obtained water‐suspensible carbon nanotubes (CNTs) were still homogeneously distributed in water a month after sonication. The microstructural development of filler networks and the uniform dispersion of MWCNTs in the presence of IL were analyzed by TEM. The apparent physical (cation–π/π–π) interaction between the MWCNTs and the IL was characterized by Raman spectroscopy, DSC, and TGA. Furthermore, high‐performance composites of natural rubber latex (NRL) and CNTs modified with IL were obtained by the liquid latex blending method. The CNTs were homogeneously distributed in the matrix and CNT–ILs improved the fatigue resistance and mechanical properties of the NRL/CNT–IL composites. This study demonstrates a simple and eco‐friendly approach to develop multifunctional advanced materials based on IL‐modified MWCNT elastomer composites. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46588. Abstract : This picture is the most intuitive manifestation of the improvement of carbon nanotube dispersion ability after CNTs have been modified with ionic liquids. Upon modification with the ionic liquids, the dispersion of carbon nanotubes was improved and the entanglement was obviously reduced.